NILAI RELIGIUSITAS DALAM TINJAUAN SAJAK “POTRET KELUARGA” KARYA WS RENDRA - Gilang Tresna; Maryana Maryana; Nursiti Fatimah; Agus Priyanto (IKIP Siliwangi, 2018)
Literature is a work created by someone who will be published later, so the work he has made can be enjoyed by many people. A literary work written by an author whose purpose to read by others, in a literary work that has been created must have to contain the values that can be taken by readers. Among the many literary works we have read that we find interesting are the poems of